Formato antologia e formato libro. Sui modi di presentazione della poesia nel Novecento (ENTHYMEMA, 2017)
This essay proposes to discuss the role of the “poetic anthology” during the twentieth century by putting it in relation to the “book of poetry”, who has obtained in the same context a consolidated role. These are is in fact two key devices when it comes to transmission and fruition of poetics (poetics of formats above poetics of forms) that have always been active in Tradition, but they are, right with the introduction in an advanced phase of modernity, in the midst of a deep functional redefinition. This redefinition is embedded in a context that can be considered as a systemic transformation where poetry is present in different ways in the new literary system of the twentieth century. Between these two formats runs a complex dialectics of interdependence and tension, a tight functional co-implication and a latent ideal opposition: on the background of which even more questions are raised due to the interplay of functions, the uses, the effects of so many different forms of poetic anthologies (as well as poetry books) practiced in our twentieth and twenty-first century.
Keywords: Poetry book; anthology; macrotext; format; contemporary poetry